Bacillus spp. and Pisolithus tinctorius effects on Quercus ilex ssp. ballota: a study on tree growth, rhizosphere community structure and mycorrhizal infection - Domenech, Jezabel; Ramos-Solano, Beatriz; Probanza, Agustin; Lucas-Garcı́a, José Antonio; Colón, Juan José; Gutiérrez-Mañero, Francisco Javier (Forest Ecology and Management, 2004)
A local species of oak (Quercus ilex ssp. ballota) was inoculated or co-inoculated with the ectomycorrhizal fungus Pisolithus tinctorius and two plant growth promoting rhizobacteria (PGPR) of the genus Bacillus (Bacillus licheniformis CECT 5106 and Bacillus pumilus CECT 5105). Effects of inoculation on growth, on N acquisition by the plant roots, changes in rhizosphere microbial communities and the degree of mycorrhization were evaluated. Only B. licheniformis promoted the growth of Q. ilex seedlings while co-inoculation of either bacterial strain with P. tinctorius had a negative effect on plant growth. Furthermore, B. licheniformis inhibited fungal growth as revealed by ergosterol/chitin analysis. As shown by phospholipid fatty acid proﬁles, the inoculation caused a slight alteration in the microbial community structure of the rhizosphere, both in the total community and the culturable populations.
Keywords: ballota; microbial community structure; mycorrhiza; PGPR; quercus ilex ssp

Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A. Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F. Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation

Efecto de la inoculación de cuatro bacterias promotoras del crecimiento vegetal sobre parámetros biométricos aéreos de plántulas de QUERCUS ILEX SSP.BALLOTA B. - Ramos, B.; Lucas García, J. A.; Santamaría, C.; Camacho, M.; Daza, A.; García, J. A. Lucas (III Congreso Forestal Español Congreso, 2001)
In the present work has studied the effect of four plant growth-promoting rhizobacteria (PGPRs) on growth of holm-oak plants (Quercus ilex ssp. ballota) in nursery before transplanting. The four strains assayed show in vitro metabolic capacities related with their action PGPR. All strains were able to increase significantly some parameters studied (high, diameter neck and dry weight). However, in the first sampling time (T1) only the strains Aur 6 and Aur 9 increased the high of the plants. In the last sampling time (T3) all strains increased the high, only Aur 6 increased the diameter neck and Cell 3, Aur 6 and Aur 9 increased the dry weight. It is important to point out that Aur 6 and Aur 9 increased the high and also the dry weight, this show that these strains enhance the general metabolism of the plants and also enhance the nutritional capacity and as a result the plants are more robust and with a better adaptative capacity.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso issue: 1 pub-location: Granada
Keywords: adaptative capacity; colonization; PGPR; Quercus ilex ssp. ballota